Design of Fir Digital Bandpass Filter with Hamming Window and Hanning Window Method for Fetal Doppler - Hartono Siswono; Widyastuti Widyastuti; Yohanes Dovan; Dyah Nur’ainingsih (Universitas Ahmad Dahlan, 2023)
DESIGN OF FIR DIGITAL BANDPASS FILTER WITH HAMMING WINDOW AND HANNING WINDOW METHOD FOR FETAL DOPPLER